The supervisor’s influence on worker safety in construction projects: a case study in northern region, Malaysia / Amirah Husna Abd Muien, Siti Hamidah Abdull Rahman, Fatin Najwa Mohd Nusa and Musmuliadi Kamaruding - Abd Muien, Amirah Husna; Abdull Rahman, Siti Hamidah; Mohd Nusa, Fatin Najwa; Kamaruding, Musmuliadi (2023)
Construction is one of the most hazardous businesses in the world, with countless accidents resulting in substantial loss of life and property damage. The fact that management conduct appears to be a key factor in workplace safety mishaps put even more attention to the matter. The connection between managerial behaviors and workers’ safety in the construction industry has not been well studied or correctly characterized. This paper is aimed at discovering those management behaviors which can significantly impact workers’ safety in construction projects. The objectives of this study are to identify the dimensions of supervisory behavior related to workers’ safety, to determine the impacts of poor supervision on workers’ safety, and lastly to offer solutions to improve bad supervisory behavior to assure workers’ safety. A quantitative study was conducted by the distribution of questionnaires, with 142 respondents taken from construction employees from different contractor firms. They were selected from contractors’ companies registered under CIDB in three Northern states: Pulau Pinang, Kedah, and Perlis. The data were analyzed by using Statistical Package for the Social Science (SPSS). Normality, Validity, and Reliability Test with Cronbach’s Alpha Coefficient has been adopted in this research. The repercussions include delays in job progress, expenditure overruns, rework, and disruption of the project’s timeline and also to the productivity of the project. The impacts include delays in work progress, expense overruns, rework, mess with the project’s schedule, and also to the productivity of the project. Based on these findings, a supervisory effort to modify bad supervising behavior may assist to protect worker safety.